Astrocytes as Guardians of Neuronal Excitability: Mechanisms Underlying Epileptogenesis - Verhoog, Quirijn P.; Holtman, Linda; Aronica, Eleonora; van Vliet, Erwin A. (Frontiers in Neurology, 2020)
Astrocytes are key homeostatic regulators in the central nervous system and play important roles in physiology. After brain damage caused by e.g. status epilepticus, traumatic brain injury or stroke, astrocytes may adopt a reactive phenotype. This process of reactive astrogliosis is important to restore brain homeostasis. However, persistent reactive astrogliosis, can be detrimental for the brain and contributes to the development of epilepsy. In this review, we will focus on physiological functions of astrocytes in the normal brain as well as pathophysiological functions in the epileptogenic brain, with a focus on acquired epilepsy. We will discuss the role of astrocyte-related processes in epileptogenesis, including reactive astrogliosis, disturbances in energy supply and metabolism, gliotransmission, and extracellular ion concentrations, as well as blood-brain barrier dysfunction and dysregulation of blood flow. Since dysfunction of astrocytes can contribute to epilepsy, we will also discuss their role as potential targets for new therapeutic strategies.